Analysis of Errors Made by Students with Low Computational Thinking Levels Using the Newmann Procedure - Inayah Wulandari; Musthofa Musthofa (Pendidikan Matematika STKIP Kusuma Negara, 2026)
Computational thinking plays a crucial role in strengthening strategies for solving complex problems. However, many students are still found to have low computational thinking abilities, which are attributed to errors occurring during the problem-solving process based on computational thinking. This study aims to analyze the errors made by students with low computational thinking abilities when solving rational number problems using the Newmann procedure. The method employed is descriptive analysis of the responses from students with low computational thinking abilities, following the Newmann procedure. The analysis revealed that comprehension errors were the most frequently observed type of error in solving rational number problems based on computational thinking indicators, particularly in problems assessing decomposition, algorithmic thinking, and generalization. Other types of errors were also identified, including reading and transformation errors in problems assessing abstraction, process errors in problems measuring decomposition, and final answer errors in problems evaluating decomposition, abstraction, and generalization. The results of this study indicate that low computational thinking abilities in students can be attributed to errors summarized in the Newmann procedure, and it offers recommendations for enhancing computational thinking by considering interventions that can minimize these types of errors.